The Relationship Between Vitamin D Levels and Severity of Menopausal Symptoms - Anıl Erturk; Nergis Kender Erturk (Genel Tıp Dergisi)
Introduction: Our aim was to investigate the relationship between menopausal symptoms and serum vitamin D levels. Methods: We analyzed 110 postmenopausal women aged between 42-65 years among menopause symptoms by using Menopause Rating Scale (MRS) questionnaire. Patients were divided into three groups according to their serum 25-OH vitamin D levels; sufficient (>20 ng/mL), insufficient (12-20 ng/mL), deficient (